Kosmetik Halal dalam Perspektif Islam: Perkembangan Industri, Tantangan, dan Inovasi Model Bisnis di Era Digitalisasi - Muhammad Naufal Faqiih; Raihan Septiawan Mubarak; Rahma Fauziah (Journal of Economics, Management, and Accounting, 2026)
The halal cosmetics industry has experienced rapid growth as part of the global Islamic economy, driven by the increasing Muslim population, greater consumer awareness of product safety, and the rising trend of the halal lifestyle. This study aims to analyze the development of the halal cosmetics industry, its challenges, and business model innovations from an Islamic perspective in the digitalization era. The study employs a qualitative method using a literature review approach by analyzing scientific articles, books, industry reports, and relevant policy documents. The findings indicate that halal cosmetics are not only required to comply with halal requirements but must also fulfill the halalan thayyiban principle, encompassing product safety, quality, and overall benefits. Despite its strong growth potential, the industry continues to face challenges related to halal certification, dependence on imported raw materials, limited halal literacy, and differences in international halal standards. Digitalization through e-commerce, blockchain technology, and Sharia-based business model innovation has become a strategic factor in enhancing the competitiveness and sustainability of the halal cosmetics industry.